2018
DOI: 10.3390/technologies6010012
|View full text |Cite
|
Sign up to set email alerts
|

Eye-Gaze Control Technology as Early Intervention for a Non-Verbal Young Child with High Spinal Cord Injury: A Case Report

Abstract: Assistive technology (AT) can be used as early intervention in order to reduce activity limitations in play and communication. This longitudinal case study examines eye-gaze control technology as early intervention for a young child with high spinal cord injury without the ability to make sounds. The young child was followed by repeated measures concerning performance and communication from baseline at 9 months to 26 months, and finalized at 36 months by field observations in the home setting. The results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…1 Qualitative studies and cases studies have found that an EGCC could be a realistic option for children with complex needs. [9][10][11][12][13][14] Parents have reported that EGCCs provided children with opportunities to demonstrate agency; they could initiate communication and express basic needs, such as thirst and pain. The EGCCs also helped children to express their personality by providing opportunities to make choices and show selfdetermination.…”
Section: Introductionmentioning
confidence: 99%
“…1 Qualitative studies and cases studies have found that an EGCC could be a realistic option for children with complex needs. [9][10][11][12][13][14] Parents have reported that EGCCs provided children with opportunities to demonstrate agency; they could initiate communication and express basic needs, such as thirst and pain. The EGCCs also helped children to express their personality by providing opportunities to make choices and show selfdetermination.…”
Section: Introductionmentioning
confidence: 99%
“…Adults are supposed to be independent and efficient. Just as all children need to explore and learn activities at younger ages, research shows that children with severe disabilities that use EGAT need opportunities in everyday life to explore activities, and demonstrate competencies [ 5 , 11 ] and gaining experiences of eye-gaze performance [ 29 , 30 ] before effectively and independently managing activities of daily living. In addition, gradually becoming more independent is part of development and personal growth for all children [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 illustrates how each dwell-spot on the eye tracker corresponded to each mole. The design of this interface was based on the literature of explicit eye gaze interfaces, where all studies with children [11][12][13][14][15][16][17] included a computer screen. In this study, the eye tracker itself played the role of the screen with dwell-spots.…”
Section: Eye Gaze Interfacesmentioning
confidence: 99%
“… 12 Children as young as 9 months of age were capable of dwelling their gaze on a target to select it with about 80% success rate, and the rate improve to 100% at 11 months. 13 However, the performance on that task cannot generalize to more complex tasks that include multiple objects.…”
Section: Introductionmentioning
confidence: 99%